Integration of Neo-Vernacular Architectural Values in the Design of Rental Apartments in Makassar City - Apriani, Widya; Nazaruddin, Nazaruddin (Journal of Engineering and Vocational Education, 2026)
Purpose of the study: This study aims to analyze and formulate the integration of neo-vernacular architectural values derived from Bugis–Makassar traditional architecture into the design concept of rental apartment buildings in Makassar City in order to create culturally contextual and functional vertical housing. Methodology: This study used a qualitative research approach with architectural design analysis. Data were collected through literature study, documentation study, and site observation in Makassar City. The analysis employed descriptive qualitative analysis to identify Bugis–Makassar architectural elements and integrate them into contemporary apartment design concepts. Main Findings: The results show that Bugis–Makassar architectural elements such as traditional roof forms, spatial hierarchy, ornamental motifs, and environmental adaptation can be transformed and integrated into modern apartment design. The proposed design combines cultural identity, environmental responsiveness, and functional efficiency through façade adaptation, zoning systems, natural ventilation strategies, and contextual building mass composition. Novelty/Originality of this study: The novelty of this study lies in the conceptual integration of Bugis–Makassar neo-vernacular architectural values into vertical residential design. This research demonstrates how traditional cultural elements can be transformed into modern apartment architecture while maintaining functional requirements and strengthening local cultural identity in urban housing development.